Dinamika Dukungan Politik Terhadap Program Makan Bergizi Gratis (MBG) di Indonesia - Luis Fiska Rahayu (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The Free Nutritious Meals (MBG) program is an Indonesian government initiative aimed at improving children's nutritional status and reducing stunting rates. Despite widespread support, the program faces a number of challenges, including food poisoning, implementation challenges, funding shortages, and suboptimal oversight. This study aims to evaluate the implementation of the MBG program based on field reports, public feedback, and central and regional government policies. The findings indicate that while the MBG program has significant potential for improving national nutrition, implementation and oversight are still needed. While the MBG program is a strategic step in improving the nutritional status of Indonesian children, its implementation remains far from ideal. Poisoning, logistical issues, and funding constraints must be addressed immediately through strengthened cross-agency coordination, improved supply chain management, and increased oversight capacity by the National Agency for National Development Planning (BGN) and regional governments. Recommendations for program strengthening include: A comprehensive evaluation of the distribution chain and production kitchens; Increased budget with a more efficient disbursement system; Community involvement in food quality monitoring; Implementation of strict food safety standards; Insurance and legal protection for beneficiaries. With improvements in these various aspects, the MBG has the potential to become a long-term program that not only reduces stunting rates but also fosters a healthy and productive generation